Epistemological foundations of Islamic economic knowledge"value of recognition" - Seyed Hossein Mir-Moezi (جستارهای اقتصادی, 2022)
The value of recognition is one of the main and important subject matters in epistemology, which directly affects the methodology of knowledge. The key question is how to recognize correct, true and valid cognitions from false, invalid and false ideas? The value of recognition consists of two theories of truth and justification. This article aims to explain and compare the theory of truth and justification in the philosophy of conventional economic knowledge and Islamic economic knowledge and its results and requirements in the methodology of this knowledge. The results of the research show that the main stream of conventional economic knowledge is "empirical compatibilist" in the theory of truth and "empirical fundamentalist" in the theory of justification; ; Although some economic philosophers, following the developments that took place in epistemology in philosophy and philosophy of science in the West, proposed and chose theories such as pragmatism, integrationism, and anarchism as the theory of truth or justification. While the Islamic philosophers are "conformist realist" in the theory of truth and "rationalist fundamentalist" in the theory of justification. Then, based on these two theories in Islamic philosophy, how to evaluate the propositions of Islamic economic knowledge in the four fields of religion, system, system development and Islamic economics has been explained.